A Sociology of Culture, Taste and Value - Stewart, S. author. aut Link
VI, 198 p.
Keywords: This book explores sociological debates in relation to culture, taste and value. It argues that sociology can contribute to debates about aesthetic value and to an understanding of how people evaluate. .